Targeting New Pharmacological Approaches for Alzheimer’s Disease: Potential for Statins and Phosphodiesterase Inhibitors - Sallustio, Fabrizio; Studer, Valeria (CNS & Neurological Disorders - Drug Targets, 2016)
Alzheimer’s disease (AD) is the most common cause of dementia among the elderly. It is pathologically characterized by diffused extracellular deposits, senile plaques, and intracellular neurofibrillary tangles in the brain, responsible for neuronal dysfunction and cell death. Memory, language and other cognitive functions can be affected to a limited extent in the initial stage called mild cognitive impairment (MCI) or in a more severe and daily life interfering manner in the later stage called dementia. Currently no effective disease-modifying treatment exists for the majority of neurodegenerative diseases. Failure of therapy aimed at affecting beta amyloid pathology has led research to investigate alternative approaches. Recent findings address statins and phosphodiesterase (PDE) inhibitors as compounds able to affect different mechanisms underlying AD. Statins could exert several effects based on their lipid-lowering and cerebral blood flow increasing abilities but also pleiotropic/antinflammatory and neuroprotective properties have been claimed. PDEs act as regulators of intracellular signaling cascades through the control of two second messengers, cyclic adenosine monophosphate and cyclic guanosine monophosphate. PDE inhibitors effects in animal models of AD have been promising and their proven safety in clinical use create high expectations for the treatment of AD. In this review, we will report main data and evidence on: 1. Current pathophysiological theories of AD in order to better understand which mechanisms lead to pathological changes and can be affected by therapies; 2. The use of statins and PDE inhibitors in animal models of AD and in humans, analyzing their mechanisms of action.
Keywords: phosphodiesterase inhibitors